Glaucoma therapy: Prescription audit and cost analysis at glaucoma clinic of BP koirala lions center for ophthalmic studies. - Sapkota, Binay (2008)
ABSTRACT: Introduction:Glaucoma is the leading cause of blindness all over the world and stands fourth in Nepal. About 67 million people are affected with glaucoma. Introduction of many new treatment modalities (prostaglandin analogues, topical carbonic anhydrase inhibitors) have improved the management of glaucoma and also caused decline in surgical interventions. But with the effective uses of these, costs of glaucoma pharmacotherapy have also escalated. The present study aims to audit the prescriptions of glaucoma patients and their costs for glaucoma medication. Objective:To audit the prescriptions and cost analysis of glaucoma therapy in the tertiary eye care hospital of Nepal. Methods:A prospective study of prescription of glaucoma patients visiting the special glaucoma clinic of BP Koirala Lions Center for Ophthalmic Studies was done from 2065 Baishakh 15 to Ashad 15 (27 April to June 29,2008). Information about costs of the medications were taken from CIMS January to April 2007 and tallied with a retailer pharmacy, located at the hospital premises, Maharajgunj, Kathmandu. Results:Average number of drugs prescribed per prescription was 1.37.41 prescriptions were in generic versions and 65 in proprietary names. Timolol bore the major portion of all generic as well as brand prescriptions (17 out of 41 prescriptions). Worldwide escalating latanoprost, Prostaglandin analogue were prescribed in six prescriptions. All the prescriptions were legible and prescription errors were minimum. 38 generic prescriptions constituted written instruction to patients regarding dose, 40 constituted written instruction to patients regarding dosing interval, 12 contained written instruction to patients regarding proper method of instillation (physician counseled the patients about this), 31 contained written instruction to patients regarding duration of therapy. POAG was the commonest type of glaucoma (54%). Mean unit cost of timolol was NRs 77.96 and that of latanoprost was NRs. 580.50. Monthly mean cost of timolol was NRs. 62.04 and that of latanoprost was NRs. 515.99. Total mean cost of timolol was NRs. 77.41 and that of latanoprost was NRs. 537.54 for the duration of therapy prescribed. Conclusion :The price variation among timolol, pilocarpine, mannitol, brimonidine, latanoprost was significant. ß blockers (timolol) were the highly prescribed medications due to their cost effectiveness. No case of polypharmacy was observed. Key words:Primary open angle glaucoma, Angle course glaucoma, Prescription audits, Glaucoma medications, Generic name, Patient adherence